A Cursory Look at the Fishmeal/Oil Industry From an Ecosystem Perspective - Shannon, Lynne; Waller, Lauren (Frontiers in Ecology and Evolution, 2021)
By supporting the fishmeal industry, are we competing with our marine predators? Should we be taking away food from our predators to subsidize agriculture? If not for human consumption, should forage fish be left in the sea for predators? Are there more sustainable alternatives to fishmeal; can the fishing industry be part of developing these? These are all pressing questions currently being posed by marine scientists, particularly in the light of the increasing aquaculture industry and associated increasing demand in recent decades for fishmeal and oil to sustain cultured fish. We concisely summarize the global context of marine sourced fishmeal and then use the South African marine ecosystem as a working example. Several species inhabiting South African waters and relying on forage fish as prey are either charismatic and important for ecotourism and/or species of conservation concern. Forage fish are an important dietary component of several commercially important fish species. In recent years the South African sardine stock has collapsed, and reduced availability of sardine off South Africa’s west coast is stressing the marine ecosystem including high profile predators, the purse seine fishery and tourism-based industries. The sardine stock collapse is also likely to increase reliance of predators on other forage fish such as anchovy. This paper draws on research into the trophic role of forage fish in marine ecosystems and ponders whether a reduced demand for fishmeal, given increasing global pressures such as climate change, could benefit our marine ecosystems, fisheries on predatory species, and our vulnerable marine predators.